A collaborative, school-based wraparound support intervention for fostering children and youth's mental health - Haight, Jessica; Gokiert, Rebecca; Daniels, Jason (Frontiers in Education, 2023)
Early mental health interventions are needed in response to a growing mental health crisis among children and youth. Schools are promising sites for early intervention because they have existing infrastructure for engaging with students. Specifically, collaborative initiatives involving community partnerships allow schools to leverage shared resources to deliver mental health support. However, more research is needed to guide the development of early interventions so that they effectively address students' mental health needs. The present study explored the role of collaborative, school mental health services in fostering children and youth's mental health, through All in for Youth, a wraparound model of support in Edmonton, Canada. Three research questions were addressed: What mental health concerns do children and youth experience? What are the factors that impact the use of collaborative school mental health services? Do collaborative school mental health services lead to perceived mental health impacts among children and youth? A multiple methods secondary analysis was conducted on school cohort data across seven elementary and junior high schools (n=2,073 students), and interview and focus group data (n=51 students, grades 2-9; n=18 parents/caregivers). The quantitative findings indicated that 42.7% of students accessed any type of mental health service across the schools, with close to equivalent service use by gender (50.2% male, 49.5% female, 0.3% genderqueer) and grade (kindergarten-grade 9; M=10%, SD=1.9%, range=6.3-13%). Participants accessed mental health services in primarily individual or combined individual and group settings (72.9%) and as an informal client (75.1%). The interview and focus group findings revealed high mental health needs among students, which were exacerbated by the COVID-19 pandemic. In response to these needs, a supportive school culture, adequate school communication, and a stable and well-resourced mental health workforce promoted access to collaborative school mental health services. Finally, mental health services supported children and youth through the experience of having a supportive relationship with a safe and caring adult, an improved capacity to cope with